Pengujian Efisiensi Pasar Bentuk Lemah pada Indeks LQ45 di Bursa Efek Indonesia Periode April 2020-April 2024 - Tyta Ripal; Ardhi Goeliling; NI Nyoman Devi; Abdul Rahim Amin; Arya Bayu Peringga Putra; I Gede Arya Pering Arimbawa; A. Fadel Muhammad (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
This research aims to find out the pattern and correlation of stock return movements on the LQ45 index in the period April 2020 - April 2024. This is related to market efficiency theory, when the market is efficient in a weak form, the fluctuating movement of the index reflects that the shares included in The LQ45 Index group is influenced by various information that occurs and is relevant to the capital market and moves randomly. However, if the price movement pattern is influenced by previous price movements, the market is inefficient in the weak form. Run-tests and autocorrelation tests are used to provide evidence of weak form market efficiency. The research results show that during this period the movement of weekly and monthly LQ45 Index returns was random so it was categorized as an efficient market in weak form. The return autocorrelation test also shows that there is no positive or negative autocorrelation, this shows that the current return movement is not influenced by previous returns.